THE INFLUENCE OF LEADERSHIP, MOTIVATION, AND DISCIPLINE ON EMPLAOYEE PERFORMANCE AT PT MERDEKA SARANA USAHA PANGKAL PINANG BANGKA BELITUNG - Siti Rochaeni; Junaidi Junaidi; Andika Andika (Syarif Hidayatullah State Islamic University Jakarta, 2020)
The company needs management related to efforts to achieve certain goals for the company. Whether an organization succeeds in achieving goals depends on the success of the individual organization in carrying out its duties. The company is said to be good if it can achieve the targets that have been set. Meanwhile, whether the company's targets are achieved depends on the performance of all employees. Performance is said to be good if employees can fulfill several things, including the quantity of work and the quality of work. PT Merdeka Sarana Usaha is one of the companies engaged in the cultivation of vanamei shrimp, but in its business activities, there are indications of a decrease in employee performance. This is known as the non-achievement of production targets in 2018 that have been set by the company.This study aims to (1) Determine the influence of leadership on the performance of PT Merdeka Sarana Usaha employees. (2) Knowing the influence of motivation on the performance of employees of PT Merdeka Sarana Usaha. (3) Knowing the effect of discipline on the performance of employees of PT Merdeka Sarana Usaha. (4) Knowing the influence of leadership, motivation, and discipline on the performance of PT Merdeka Sarana Usaha employees. The source of the data used is primary data obtained through the results of a questionnaire on respondents of all employees of PT Merdeka Sarana Usaha.The results showed that leadership did not affect employee performance at PT Merdeka Sarana Usaha, motivation affected employee performance at PT Merdeka Sarana Usaha, and discipline affected employee performance at PT Merdeka Sarana Usaha, and together with leadership, motivation, and discipline influenced the performance of PT Merdeka Sarana Usaha employees.